A Histomorphological Study of Meningiomas According to Latest CNS 5 th Edition WHO Classification 2021 and Co-relation of Grading with Ki-67 Proliferation Index - Navdeep Khangura; Sonal Bhati; Gunjan Bhatia; Namita Goyal; Sandeep Kaur Khangura (Journal of Medical Sciences and Health)
Introduction: Meningiomas are group of mostly benign and commonest non glial tumours. The revised 5th edition of WHO 2021 classification of tumours of the central nervous system categorized meningiomas into single type, with its broad morphological spectrum reflected in 15 subtypes. Aim and Objectives: The main objective of new classification was on grading of tumour along with molecular emphasis. New classification also favoured use of Arabic numerals for grading compared to traditional Roman numerals. The biological behaviour and recurrences are difficult to predict from morphology alone, so Ki-67 Proliferation Index aide in grading of meningioma. The aim of study was to evaluate the histomorphology and grade of meningiomas according to CNS 5th edition classification and correlating the grading and subtyping of meningiomas with Ki-67 Proliferation Index. Materials and methods: This was a cross-sectional observational study of 18 months duration. Sample size included 30 cases. After processing and staining with H and E, cases were classified according to WHO 5th edition classification; Ki-67 staining was done on respective slides and proliferation index was calculated. Results: Our study observed that meningiomas were more common in female population (73.3%) with common age of presentation was 4th and 6th decade of life and the most common subtype being transitional meningioma (46.66%). Majority of cases belonged to CNS WHO grade 1 (86.66%) followed by grade 2 (10%) and grade 3 (3.33%). Average Ki-67 PI for grade 1, grade 2 and grade 3 tumours were 3.57,12.47 and 23.20 respectively. Significant co-relation was found between higher grades of meningioma and Ki-67 Proliferation Index. Conclusion: Histomorphology along with Ki-67 proliferation index is an important diagnostic tool for grading of meningiomas and helps the surgeon in establishing better follow up criteria and long-term management strategies for the benefit of the patient.